(untitled) (Journal of Contemporary Philology, 2024)
This study focuses on specific linguistic markers in the chief prose work of American poet and artist Theresa Hak Kyung Cha, Dictée, that display commitment in utterance. Theresa Hak Kyung Cha’s Dictée is an autobiographical work which explores the protagonist’s identity in relation to the author’s personal family history as well as historical events as well as numerous references to female mythological figures. In it, layers of the self are further articulated through a specific relationship to the audience, and through a fragmentary form that resists genre classification. By focusing on the linguistic concept of commitment in speech act, the present study explores how in Dictée Cha develops the multilingual subject through voicing. By focusing on the pronoun use, the role of gerund in altering the syntax and the passage between French and English languages, this study exposes the link between the crafting of the speech act and of the multilingual self. We conclude that textual fragmentation in Dictée should not be read as disintegration or inability to attain utterance or a questioning of the woman’s multilingual identity. Not only is fragmentary expression necessary for capturing the various elements of the multilingual self, but it also helps underscore the link between writing and speech as the site of the multilingual subject.